2005
DOI: 10.1051/0004-6361:20041055
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the halo density profile using HI flaring in the outer Galaxy

Abstract: Abstract. The observed flaring of HI disk in the outer region of galaxies has been used in the past to determine the shape of the dark matter halo. Previous studies based on this concept suggest a slightly oblate halo (axis ratio ∼0.8) for our Galaxy. We reinvestigate this problem by calculating the HI scaleheight in the outer Galaxy to a larger radial distance, and by studying its dependence on the shape and the density profile of the halo. We find that a simple isothermal infinite halo of any shape-oblate or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 42 publications
5
79
0
Order By: Relevance
“…First we discuss non-singular spheroids with flattening q (see e.g. Olling & Merrifield 2001;Narayan et al 2005),…”
Section: Flaring Caused By a Spheroidal Halomentioning
confidence: 99%
See 3 more Smart Citations
“…First we discuss non-singular spheroids with flattening q (see e.g. Olling & Merrifield 2001;Narayan et al 2005),…”
Section: Flaring Caused By a Spheroidal Halomentioning
confidence: 99%
“…Oblate halos have q < 1, prolate q > 1. ρ 0 is the density at the center, R c defines the core radius, and p is the power index (Narayan et al 2005). We consider the case p = 1 first.…”
Section: Flaring Caused By a Spheroidal Halomentioning
confidence: 99%
See 2 more Smart Citations
“…Olling (1995) demonstrated that the shape of the flaring H i layer is affected by the flattening of the dark matter component. Olling & Merrifield (2000, 2001, and later Narayan & Jog (2002), Kalberla (2003), Narayan et al (2005), and Kalberla et al (2007) applied this basic idea to model the Milky Way mass distribution using fullsky H i data. According to these investigations, it became evident that stellar flaring is also expected to be observed (Jog 2007).…”
Section: Introductionmentioning
confidence: 99%